PGC-1 ALPHA PROTEIN EXPRESSION PROMOTER AND SLOW-TO-FAST MUSCLE CONVERSION INHIBITOR (2019)
Enterococcus faecium Enterococcus faecium A food or a drink, including: R30 strain (NITE BP-01362) or a processed product thereof; and at least one additive selected from the group consisting of a sweetener, a bittering agent, and acidulant. A method for promoting expression of PGC-1α protein, or preventing conversion of a slow twitch muscle into a fast twitch muscle, the method including: administering R30 strain (NITE BP-01362) or a processed product thereof to a subject in need thereof.